Comparison of Pushover Method and Direct Displacement Method in Earthquake Load Analysis with Performance-Based Design Concepts - I Nengah Sinarta; I Made Bagastia Pinandika (U Karst, 2020)
The development of earthquake-resistant building designs led to developing an analysis method for earthquake loads, one of the performance-based methods. This method uses structural displacement as an approach. The purpose of this analysis method was to guarantee the structure's performance so that it will be able to withstand forces due to earthquake loads. In this paper, an analysis of a building structure's design was more reliable with applicable regulations in Indonesia and determined building performance based on FEMA 356. The study was carried out using the direct displacement method and the pushover analysis method, with the displacement targets and structure performance levels being compared with each other. Based on these results, it can conclude that the use of the direct displacement method and pushover analysis can produce almost the same displacement target values and structure performance levels. Comparison using pushover analysis design performance targets can be fulfilled so that the Direct Displacement Based Design Method can be used in structures. The total displacement value of the x-x (δT) direction is 0.300 m, and the y-y course is 0.115 m.